The Puzzle of Japanese Software. - Cusumano, Michael A. (Communications of the ACM, 2005)
In this article, the author presents solutions to the problems associated with the computer software developed by the Japanese companies. Japanese do make many software products, but they are generally written with Japanese interfaces, many are for mainframe computers, and they are often heavily tailored to Japanese needs, such as for generating local maps or doing local accounting and taxes. Japanese corporate users have traditionally relied on mainframes and were slow to move to personal computers that used a wide variety of relatively inexpensive products. Japanese corporate IT departments still seem to prefer expensive custom-built software, albeit with increasing amounts of packaged U.S. software products mixed in, such as databases and operating systems. Another problem is that Japan's computer producers competed for decades with their own incompatible proprietary standards and were slow to adopt global platforms such as Windows and Unix, making it even more difficult for them to participate in the global software products business. Many Americans and Europeans, and some Japanese, also believe that Japans education and employment systems suppress the type of creativity needed to cultivate software programmers with a creative product mentality.